Pengaruh Kegiatan Ekstrakurikuler, Manajemen Waktu, dan Motivasi Belajar Terhadap Prestasi Belajar Matematika Siswa SMP Kelas VIII - Ahmad Thariq Rasyidi; Asdar; Baso Intang Sappaile (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2020)
This study was conducted to determine the influence of extracurricular activities, time management, and learning motivation towards student’s mathematics learning achievement of grade VIII SMP. This research is ex post facto research which is causality with research sample counted 62 students from class VIII SMP selected by using cluster random sampling. Technique of collecting data using instrument: (1) questionnaire of extracurricular activities, (2) questionnaire of time management, (3) questionnaire of learning motivation, and (4) test result of mathematics learning. Data were analyzed with descriptive statistics and inferential statistics with path analysis. The result of the research shows that: (1) the student's 'extracurricular activities is in the high category, (2) the student's time management is in the high category, (3) the student's learning motivation is in the high category, (4) student’s mathematics learning achievement in the medium category (5) student’s extracurricular activities, time management and learning motivation have no effect together towards student mathematics learning achievements, (6) student’s extracurricular activities and time management related together to student’s learning motivation, (7) student’s extracurricular activities have no direct positive effect on student’s mathematics learning achievement, (8) student’s time management directly negative effect on student’s mathematics learning achievement, (9) student’s learning motivation directly positive effect student’s mathematics learning achievement, (10) student’s extracurricular activities have no effect indirectly towards mathematics learning achievement through student’s learning motivation, (11) student’s time management indirectly effect towards mathematics learning achievement through student’s learning motivation.